Continuing and extending resistance and struggle: The role of Robben Island 1963-1976 - Buntman, Fran (My University, 1994)
Resistance and anti-apartheid politics in South African are generally considered to have been greatly diminished in the aftermath of the Sharpeville Massacre of 1960 and the Soweto and student uprisings from June 16, 1976. One useful way of thinking about Robben Island' from 1963-1976 is in light of these dark days of struggle. On the one hand, the emergence of Robben Island as a political prison was a consequence of state power and repression, and the ability of the National Party government to suppress most of the opposition in the country. On the other hand, Robben Island was an important area where resistance against oppression and struggles against apartheid were both continued and extended, often under the most difficult conditions. The idea that a serious and intense political struggle against apartheid and its attendant racism, brutality and inhumanity continued on Robben Island prison is the argument framing this paper. It is necessary to begin by looking at the broader political context of the 1960s. One can then elaborate on the nature of the political prison, and the responses to it.
African Studies Seminar series. Paper presented 17 October, 1994
Keywords: Robben Island (South Africa). History; Prisons. South Africa